Determination of potential distribution in a three-barrier structure - Yodgorova, D.M.; Zoirova, L.X.; Karimov, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Model m₁-p-n-m₂ structures with three barriers were considered; construction and technology of manufacturing the three-barrier m₁-pAlGaInAs-nGaAs-m₂ structure are presented. Experimental methods to determine voltages across every junction of the three-barrier structure were proposed. The mechanism of current transport when changing the blocked p-n junctions and Schottky barriers were explained. It was shown that, at both polarities of operating regime, current characteristics are determined by blocked junctions. The obtained results are of interest for research of properties of three-barrier and similar phototransistor structures in response to external influences.